PPP1R21 homozygous null variants associated with developmental delay, muscle weakness, distinctive facial features, and brain abnormalities. Issue 3 (25th June 2018) - Suleiman, J.; Al Hashem, A.M.; Tabarki, B.; Al‐Thihli, K.; Bi, W.; El‐Hattab, A.W.
Abstract : We present 3 children with homozygous null variants in the PPP1R21 gene. A 3‐year‐old girl had profound developmental delay, hypotonia and weakness, poor feeding, recurrent chest infections and respiratory failure, rotatory nystagmus, absent reflexes, and a homozygous nonsense variant c.2089C>T (p.Arg697*). A 2‐year‐old boy had profound developmental delay, weakness and hypotonia, recurrent chest infections and respiratory distress, undescended testes, rotatory nystagmus, hyporeflexia, and a homozygous nonsense variant c.427C>T (p.Arg143*). An 11‐year‐old girl with profound developmental delay, weakness and hypotonia, stereotypic movements, growth failure, hyporeflexia, and a homozygous frameshift variant c.87_88delAG (p.Gly30Cysfs*4). In addition, these children shared common facial features (thick eyebrows, hypertelorism, broad nasal bridge, short nose with upturned nasal tip and broad low‐hanging columella, thick lips, low‐set ears, and coarse facies with excessive facial hair), and brain abnormalities (cerebellar vermis hypoplasia, ventricular dilatation, and reduced white matter volume). Although PPP1R21 has not yet been linked to human disease, the consistency in the phenotype of individuals from unrelated families, the nature of the variants which result in truncated proteins, and the expected vital role for PPP1R21 in cellular function, all support that PPP1R21 is a novel disease‐associated gene responsible for the phenotype observed in these individuals. Abstract :